1995
DOI: 10.1046/j.1471-4159.1995.64051988.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Neuronal‐Specific Protein that Stimulates the Activity of Cdk5

Abstract: Cyclin‐dependent kinase, Cdk5, has been identified in neural tissue in connection with neurofilament and τ protein phosphorylation. This report describes the characterization of a 62‐kDa protein that copurifies with Cdk5 from rat spinal cord homogenates. Dissociation of the protein from neural Cdk5 is concomitant with a reversible loss in kinase activity. Amino acid sequence information from tryptic peptide fragments was used to clone the complementary DNA from rat brain. A single full‐length cDNA was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 0 publications
0
49
0
1
Order By: Relevance
“…It has been found that Cdk5 interacts with munc-18 in vivo and in vitro and phosphorylates munc-18 in vitro (37,38,61). Munc-18 is also present in ␤-cells where it is thought to operate as a negative regulator of exocytosis (62).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that Cdk5 interacts with munc-18 in vivo and in vitro and phosphorylates munc-18 in vitro (37,38,61). Munc-18 is also present in ␤-cells where it is thought to operate as a negative regulator of exocytosis (62).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the ubiquitous distribution of Cdk5, the P35 transcript is present predominantly in the forebrain (Ohshima et al, 1996;Uchida et al, 1994) in cells of neuronal lineage (Delalle et al, 1997). Other activators of Cdk5 include 2 neuronspeci c proteins, the P39 protein (Tang et al, 1995), and the vesicle trafficking-associated protein, Munc-18 (Shetty et al, 1995). Interestingly, cyclin-D and cyclin-E molecules, which regulate Cdk activity in proliferating cells, bind but do not activate Cdk5 (Guidato et al, 1998;Miyajima et al, 1995;Xiong et al, 1992).…”
Section: Dk5mentioning
confidence: 99%
“…Like other members of the cyclin-dependent kinase family, cdk-5 activity requires association with a regulator, and recent studies have identified two homologous cdk-5 activators, p35 and p39flCksal (Ishiguro et al, 1994;Lew et al, 1994;Tsai et al, 1994;Tang et al, 1995). A further unrelated stimulator of cdk-5 activity, p67, which is identical to Munc-18, a component of synaptic vesicle fusion protein complexes, has also been described (Hata et al, 1993;Shetty et al, 1995). The relationship between p35 /p39 nck5ai and Munc-18 is unclear, and the relative potencies in stimulating cdk-5 activity by these different activators are not established.…”
mentioning
confidence: 99%